The Monetary Policy in Indonesia: in the Perspective of Islamic Economics - Iwan Wisandani; Sri Iswati; Rifki Ismal (UIN Sunan Gunung Djati Bandung, 2017)
The writing is based on my concern on the monetary policy in Indonesia which is not fully in accordance with the Islamic teaching. Among all, the monetary policy doesn’t pay attention to the real sector. It can be seen from the sectorial dichotomy between the real and monetary sectors whereas in Islamic economics, monetary policy is only a representative of the real sector. The paper is a literary research with the approach of comparative study between Islamic monetary policy and the monetary policy employed in Indonesia. The research result is a composition of a transmission model from the perspective of Islamic economics which is based on BI Return (sharing) by creating a diagram and then explaining some thoughts of Muslim and western economists such as Stieglitz to create a monetary policy which gets along with the real sector. The model is an observational result to the monetary condition in Indonesia which is then compared to Islamic monetary thought. This model will gain good result when all transmissions of monetary policy are applied effectively.